PEMAHAMAN TENTANG PEMELIHARAAN, NAFKAH DAN PENGANGKATAN ANAK DALAM HUKUM ISLAM - Zulpan Efendi Hasibuan (IAIN Padangsidimpuan, 2021)
This paper tries to explain the concept of child care, maintenance and adoption in Islam in terms of the perspective of children's rights in the family in Islamic law and several decisions made by the United Nations Convention on the Rights of the Child (CRC). The aim of this paper is to contribute to a better understanding of the Islamic view of child rearing, child support and adoption.